2011
DOI: 10.1186/1742-4690-8-72
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection of thymocytes inhibits IL-7 activity without altering CD127 expression

Abstract: BackgroundThymic function is altered in HIV infection and characterized by dysregulation of the thymic epithelial network, reduced thymic output and ultimately an impaired naïve T-cell pool. The IL-7/IL-7 receptor (IL-7R) signalling pathway is critical for the maturation and differentiation of thymocytes. HIV infection is associated with a decrease in IL-7Rα (CD127) expression and impaired CD127 signalling in circulating CD8+ T-cells; however, little is known about the effect of HIV on CD127 expression and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(42 reference statements)
2
6
1
Order By: Relevance
“…In the present study, despite the high level of CD127 expression on CD8 + T cells that accompanied long-term effective HAART, CD8 + T cells derived from HIV+ individuals were less responsive to IL-7 with respect to downregulation of mCD127 and induction of sCD127. This decreased sensitivity of CD8 + T cells from effectively treated HIV+ individuals is in line with previous work from our group [32]. Since CD132 is constitutively expressed and has even been shown to be upregulated on T cells from HIV+ patients [7], any reduction in IL-7 response is unlikely due to lack of the IL-7R complex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, despite the high level of CD127 expression on CD8 + T cells that accompanied long-term effective HAART, CD8 + T cells derived from HIV+ individuals were less responsive to IL-7 with respect to downregulation of mCD127 and induction of sCD127. This decreased sensitivity of CD8 + T cells from effectively treated HIV+ individuals is in line with previous work from our group [32]. Since CD132 is constitutively expressed and has even been shown to be upregulated on T cells from HIV+ patients [7], any reduction in IL-7 response is unlikely due to lack of the IL-7R complex.…”
Section: Discussionsupporting
confidence: 90%
“…In concordance with these results, subsequent studies in humans have reported the presence of a more robust CD8 + T cell response in HIV nonprogressors [25][26][27]. We and others have shown that, in the face of their importance in controlling viral replication, CD8 + T cells, as well as thymocytes and Th17 cells, retain impaired responsivity to IL-7 in virally suppressed HIV-infected individuals [28][29][30][31][32].…”
Section: Introductionsupporting
confidence: 80%
“…Thymocytes were infected in vitro with a clinical isolate HIV cs204 following previously described methods [26]. Briefly, prior to infection, thymocytes were resuspended to a concentration of 2x10 6 cells/ml in McCoys 5A media with polybrene (Sigma-Aldrich) (3 μg/ml) for 1 hour at 37ºC.…”
Section: In Vitro Hiv-1 Infection Of Thymocytesmentioning
confidence: 99%
“…The role of IL-7 in thymopoiesis is multifaceted, promoting thymocyte proliferation and survival by upregulating anti-apoptotic protein Bcl-2 and downregulating pro-apoptotic protein Bax [ 34 ]. GH can modulate genes committed to distinct biological activities of thymic epithelial cells, including expression of this cytokine [ 35 ].…”
Section: Discussionmentioning
confidence: 99%